PENONAKTIFAN POLIS SECARA SEPIHAK OLEH PERUSAHAAN ASURANSI AKIBAT PELANGGARAN ITIKAD BAIK DARI NASABAH PADA PT. PRUDENTIAL LIFE ASSURANCE - Ririn Kusumayanti, Ni Luh Putu; Sukranatha, Anak Agung Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013)
As a big company needed a responsibility, especially for service users. Therefore, this paper will discuss the factors deactivation policy unilaterally by the insurance company as well as how the resolution of these issues. Deactivation policy can be regarded as a cancellation of the agreement in the absence of good faith of either party. Because, the filling SPAJ costumers provide information about the history of the disease is not true self and identity. Completion due to deactivation policy that the company would not return the cash value of the premium is therefore due to costumer error itself that ssince the beginning has no good faith.
Keywords: Deactivation, Insurance, Policy, Violation